Strategic partnership in new multipolar world order: European Union’s ‘Three-Step Strategy’. Theory and empirical evidence in the European Union from a multidimensional approach - Podadera-Rivera, Pablo; Garashchuk, Anna (My University, 2018)
The EU has developed a ‘three-step strategy’, which pre-supposes strategic partnerships, firstly, with traditional post-Second World War Western partners, secondly, with the anticipated advantage of regional and inter-regional organization, and, thirdly, with the involvement of emerging powers in a new multipolar world order. However, there are some uncertainties with regard to the relationship between bilateral ‘strategic partnerships’ and the EU’s regional and inter-regional ‘strategies’. The present paper aims to investigate the role of strategic partnership and international institutions in new multipolar world order, to compare these concepts of strategic partnership with the realities of regional integration, and to match the bilateral and multilateral approaches toward strategic partnership. At the same time, the paper will offer an analysis of the six regional organizations in order to compare bilateral ‘strategic partnerships’ and the EU’s regional ‘strategies’, simultaneously applying both techniques: the binary logistic model and the synthetic index of strategic partner suitability.
Keywords: Alianzas estratégicas de empresas; Multilateralism; Strategic partnership; Regional integration; Binary logistic model; Synthetic index